KARAKTERISTIK KEPRIBADIAN KETUA KELOMPOK TANI DAN HUBUNGANNYA DENGAN MOTIVASI KERJANYA DI KECAMATAN MOJOLABAN KABUPATEN SUKOHARJO - Purwadi Purwadi; Sugihardjo Sugihardjo; Dwiningtyas Padmaningrum (Universitas Sebelas Maret, 2006)
Leader's behaviour characteristic is a dynamic organization of a psykological system existing inside the leader that in turn can help in creating a leadership style. Such behaviour characteristic includes interest, attitude and need brought by some one I his/her work situation. In this case, everyone has so different characteristics can affect a leader for interacting and integrating with other person as well as way of encountering a problem and finding the problem solving (Stoner and Wankel, 1986). The research aims to study behaviour characteristic of farmer group leader, to study the work motivation level of the group leader, and to study the relationship between behaviour characteristic and the farmer group leader's motivation in Sub District Mojolaban, Regency Sukoharjo. A fundamental method used in study is a descriptive method. Meanwhile the population is all farmer group leaders in Sub District Mojolaban. Sampling technique employed is census. Type and source ofdata includes primary and secondary data. Technique of collecting data used in the study are observation, interview and dokumentation. For finding out the motivation level, it is measured by suing interval formulation. While for finding out the relationship between behaviour characteristic and the farmer group leader's motivation, it uses Rank Speaman correlation test (rs). The result of research shows .that there is a significant relationship between creativity and work motivation, self-confidence and work motivation, and, influencing as well as dominating power and work motivation. Meanwhile, objectivity, tolerance and extroversion have insignifcant relationship with work motivation.